Theses and Dissertations from ULisboa to the world a case study on the international visibility of academic publications in the institutional repositories of the University of Lisbon - Melo, Luiza Baptista (2021)
Focused on the collection of theses and dissertations, the aim of the following study is to look to the scientific production of ULisboa and analyse the international visibility of it through the statistical report of these two institutional repositories for the last 10 years (2010-2019). The final goal is to demonstrate how the use of institutional repositories contributes to enhance science dissemination, research and researchers’ visibility and promotes the access to knowledge, improving the quality of the information available on the web. For this purpose, the total number of thesis and dissertations of the ULisboa, archived in both repositories, were collected, for the period 2010-2019 (10 years of implementation of the institutional repositories). Usage statistics (views and downloads) were obtained as well as the home countries of these accesses. All the collected data were analysed. Results show us that the number of thesis and dissertation archived in the repositories has been growing, as well as their use (views and downloads) is very significant in both repositories.